Deterioration of High-Moisture Corn - McMahon, Michael E. (1975)
Two small, leaky silos were filled with normal high-moisture corn (HMC), and two with HMC severely infested by Helminthosporium maydis. Counts of mesophilic bacteria, lactobacilli, coliforms, yeasts, and molds were made on corn samples as received and periodically thereafter during 220 days of storage. Temperature and gas levels also were monitored. Sequential changes in the populations of lactobacilli, yeasts, and molds were determined during spoilage of HMC. These population changes were compared on the basis of the variables encountered in the present study as well as with the results of previous studies conducted on normal HMC stored under adequate conditions. Heavy infestation by H. maydis had no appreciable effect on HMC preservation.